Influence of crank length on cycle ergometry performance of well-trained female cross-country mountain bike athletes - Macdermid, P. W.; Edwards, A. M. (European Journal of Applied Physiology, 2010)
The aim of this study was to determine the differential effects of three commonly used crank lengths (170, 172.5 and 175 mm) on performance measures relevant to female cross-country mountain bike athletes (n = 7) of similar stature. All trials were performed in a single blind and balanced order with a 5- to 7-day period between trials. Both saddle height and fore-aft position to pedal axle distance at a crank angle of 90° was controlled across all trials. The laboratory tests comprised a supra-maximal (peak power-cadence); an isokinetic (50 rpm) test; and a maximal test of aerobic capacity. The time to reach supra-maximal peak power was significantly (P < 0.05) shorter in the 170 mm (2.57 ± 0.79 s) condition compared to 175 mm (3.29± 0.76 s). This effect represented a mean performance advantage of 27.8% for 170 mm compared to 175 mm. There was no further inter-condition differences between performance outcome measurements derived for the isokinetic (50 rpm) maximum power output, isokinetic (50 rpm) mean power output or indices of endurance performance. The decreased time to peak power with the greater rate of power development in the 170 mm condition suggests a race advantage may be achieved using a shorter crank length than commonly observed. Additionally, there was no impediment to either power output produced at low cadences or indices of endurance performance using the shorter crank length and the advantage of being able to respond quickly to a change in terrain could be of strategic importance to elite athletes.